Validation of Malay version body self-image questionnaire among Malaysia's young adults - Joo, Lim Chien (2017)
Introduction: It is undeniable that how an individual perceive their appearance brings substantial impact on their quality of life, in terms of their social life, self-esteem and others. The problem has increased the awareness of researchers worldwide to further explore in this area. Body Self-Image Questionnaire is developed to measure body image perceptions; nonetheless, due to the cultural, language and environmental differences between western and eastern population, the validity and reliability need to be established before it can be used. Objectives: To determine the validity and reliability of the Malay version Body Self-Image Questionnaire among young adults in Malaysia, and to determine the invariance of the translated Malay version of Body Self-Image Questionnaire among gender in young adults in Malaysia. Methods: A cross-sectional study involved web-based survey was employed in this study among young adults in Malaysia. The study had 2 phases: Phase 1 exploratory factor analysis (EFA) and Phase 2 confirmatory factor analysis (CFA) and multi-group analysis. Participants were recruited using snowball sampling method. Descriptive, exploratory factor analysis, confirmatory factor analysis and multi group analysis were applied in the statistical analysis. Results: A total of 688 respondents participated in this study, Phase 1 EFA consisted 188 respondents; Phase 2 CFA and multi-group analysis consisted 500 respondents. For Phase 1 study, the majority of the respondents were female (67%), Malay (93.6%), single (80.9%) and students (56.4%). Results for EFA showed factor loading of all the items ranged from 0.329 to 0.921, and communalities ranged from 0.338 to 0.780. The final measurement modelusing CFA had fit indices: CFI = 0.927, TLI = 0.913, SRMR = 0.075, RMSEA = 0.053 (90%CI: 0.047, 0.060), CF fit = 0.203. The fit indices were within the acceptable range. The composite reliability ranged from 0.736 to 0.857. For multi group analysis, weak measurement invariance was achieved but not strong and strict measurement invariance. Conclusion: The results of EFA retained all the items and re-grouped them into 4 factors. The final model for Confirmatory Factor Analysis showed good model fit, valid and reliable after removing six items. The translated Malay version of Body Self-Image Questionnaire consisted of four factors with 21 items. The Measurement of Invariance test’s results among gender showed that gender is invariant in the measurement models. The questionnaire is valid and reliable to be used among young adults in Malaysia. Keywords: Body Self-Image Questionnaire, young adults, Malaysia, validity, reliability